Auditor Readiness in Preparing Extended External Reporting (In accordance with ISAE 3000 Revised) - Akie Rusaktiva Rustam; Rika Nur Widiastutik; Made Dudy Satyawan (Master of Accounting Universitas Trunojoyo Madura, 2023)
Increased publication regarding Extended External Reporting (EER) has encouraged the IAASB to develop Extended External Reporting (EER) guidelines, namely ISAE 3000 revised, to implement standards in sustainable reporting engagements. This research aims to determine how prepared auditors are in preparing Extended External Reporting according to ISAE 3000 revised. This research uses an interpretive paradigm, with qualitative methods and a case study approach. The data collection technique is interviews and observation non-participation. From the research results, it was concluded that auditors have sufficient knowledge regarding Extended External Reporting in accordance with ISAE 3000 revised. However, auditors do not understand this in depth. Extended External Reporting, according to ISAE 3000 revised, is new and has not been mandatorily disclosed in Indonesia.